If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1 + x) = 3(x + 4) (1 * 2 + x * 2) = 3(x + 4) (2 + 2x) = 3(x + 4) Reorder the terms: 2 + 2x = 3(4 + x) 2 + 2x = (4 * 3 + x * 3) 2 + 2x = (12 + 3x) Solving 2 + 2x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + 2x + -3x = 12 + 3x + -3x Combine like terms: 2x + -3x = -1x 2 + -1x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + -1x = 12 + 0 2 + -1x = 12 Add '-2' to each side of the equation. 2 + -2 + -1x = 12 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 12 + -2 -1x = 12 + -2 Combine like terms: 12 + -2 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10
| 9x+70=360 | | 2x(x-4)(x+8)=0 | | 3(5p-3)=5(p-1) | | 14x-3(2x-5)+2(5x-3)=6-5(2x-9) | | 3(y+30)=6y-4 | | 5(v-5)+3(v+2)=-4v+7+3v-2 | | 3(x+5)=5x+2.5 | | 117=6x-12+3x+3 | | (34-2)y=8 | | 8(5x-3)+4(1-8x)=3x-8+3x-2 | | 4u^2-2u=0 | | 10x5/2 | | 2p-10)/(8p-40) | | 6(9d)=3d | | 180=x+(0.05+x) | | (9x-2y)-(6x+2y)= | | 6(x-4)-4=8 | | 4logx-3logx=12 | | 238=16t^2+32t | | Xy=5x-2 | | x=13+0.75y | | 4lgx^3-3lgx^2=12 | | (5x-3)/3=4 | | 4logx^3-3logx^2=12 | | (-7)=g+(-5) | | 5a+1=8 | | 5a+56=-56 | | U-24=(-27) | | 5x+2y+30=0 | | 28=w-(-5) | | (12.50-1.95)x=125 | | 3/2x-4 |